Drug-related pityriasis rubra pilaris with acantholysis - Gajinov, Zorica T; Matic, Milan B; Djuran, Verica D; Vuckovic, Nada; Prcic, Sonja T; Vujanovic, Ljuba M (Vojnosanitetski pregled, 2017)
Introduction. Acantholysis is rarely reported histological feature of Pityriasis rubra pilaris (PRP), recently recognized as having diagnostic specificity for differentiating PRP from psoriasis. Case report. Adult male patient one week after the introduction of simvastatin had experienced pruritic erythemo-squamous eruption on head and upper trunk that in a month progressed to erythrodermia, with islands of sparing. Histological picture combined pemphigus-like acantholysis with alternating hyper- and parakeratosis, follicular plugs and dermal inflammation, and confirmed the clinical diagnosis of classic adult type 1 PRP. Acitretin therapy resulted in a resolution of skin disease. Patch test with simvastatin was negative, scratch test was positive, and it was estimated that potential risk of oral challenge with simvastatin outweighed actual need for it. Drug triggering PRP episode is the most likely explanation for temporal relation between the start of simvastatin treatment and skin eruption. Conclusion. In management of rare inflammatory skin disease, such as PRP, we have to carefully observe and evaluate not only diagnostic features but possible external influences on its course also. Key words:pityriasis rubra pilaris; simvastatin; diagnosis; drug therapy; treatment outcome.
Keywords: Simvastatin; Pityriasis Rubra Pilaris; Pityriasis